Compliance of Nurses in Carrying Out Initial Assessment of Hospital Inpathement - Wirananda, Abdi; Kristina, Tri Nur; Dwiantoro, Luky (GLOBAL HEALTH SCIENCE GROUP, 2024)
Initial assessment of hospital inpatients is an important component of patient care, ensuring appropriate treatment planning and improving patient outcomes. Nurses' adherence to initial assessment protocols is critical to maintaining the quality and safety of patient care. This study aims to evaluate nurses' compliance in implementing initial assessment of hospital inpatients and to identify factors that influence nurses' compliance with established protocols. Methodology: This research adopts an approach scoping review with the framework developed by Arksey and O'Malley. Research includes searching articles through databases Google Scholar and Scopus with the keyword